1988
DOI: 10.1177/070674378803300703
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy and Safety of Alprazolam and Desipramine in Depressed Outpatients

Abstract: Fifty-two adult depressed outpatients fulfilling Research Diagnostic Criteria for Definite Major Depressive Disorder were enrolled in a double-blind study comparing the antidepressant effects of alprazolam versus desipramine. Twenty-nine patients completed the seven week (one week placebo followed by six weeks of active drug) study. The mean daily dose of alprazolam and desipramine at study termination was 3.34 mg and 192 mg respectively. Based on psychometric ratings of depression (Hamilton Scale) and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The dropout rate was significantly greater with TCA in 2 studies [46,51]; in Ansseau et al [53], it was significantly more common with diazepam than with amitriptyline due to ineffectiveness after 2 weeks. Adverse reactions, such as anticholinergic symptoms, were significantly more frequent with TCA in 5 studies [42,[44][45][46]53], but no differences were observed between TCA and BZD in 3 other reports [41,47,52].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 95%
See 2 more Smart Citations
“…The dropout rate was significantly greater with TCA in 2 studies [46,51]; in Ansseau et al [53], it was significantly more common with diazepam than with amitriptyline due to ineffectiveness after 2 weeks. Adverse reactions, such as anticholinergic symptoms, were significantly more frequent with TCA in 5 studies [42,[44][45][46]53], but no differences were observed between TCA and BZD in 3 other reports [41,47,52].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 95%
“…Dropout rates were estimated to be approximately similar for both medication classes in 4 studies [43,45,47,52]. However, in Hubain et al [52], a significantly greater number of alprazolam-treated patients dropped out of the study (due to ineffectiveness) than amitriptylinetreated patients.…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these characteristics, benzodiazepines are best suited for use on an as-needed basis. Alprazolam is one of the most widely used benzodiazepines, and it has been found to confer a unique antidepressant effect, unlike other benzodiazepines, which typically tend toward the opposite 68–70. Thus, for an individual with a mix of depressive symptoms and situational anxiety, alprazolam may be a good option.…”
Section: Treatmentmentioning
confidence: 99%
“…Unwanted adverse effects can be limited by gradual titration to an effective dose. Alprazolam also has another advantage over the older benzodiazepines in that it may have an antidepressant effect, whereas most other benzodiazepines have a depressant effect [Remick et al, 1988;Schatzberg and Cole, 1978]. Daytime drowsiness is the main side effect of BZ, but this usually subsides after several days of treatment or can be controlled by dosage adjustment.…”
Section: Specific Medicationsmentioning
confidence: 99%